T cell lymphoma and secondary primary malignancy risk after commercial CAR T cell therapy - Ghilardi, Guido; Fraietta, Joseph A.; Gerson, James N.; Van Deerlin, Vivianna M.; Morrissette, Jennifer J. D.; Caponetti, Gabriel C.; Paruzzo, Luca; Harris, Jaryse C.; Chong, Elise A.; Susanibar Adaniya, Sandra P.; Svoboda, Jakub; Nasta, Sunita D.; et al. (Nature medicine, 2024)
We report a T cell lymphoma (TCL) occurring 3 months after anti-CD19 chimeric antigen receptor (CAR) T cell immunotherapy for non-Hodgkin B cell lymphoma. The TCL was diagnosed from a thoracic lymph node upon surgery for lung cancer. The TCL exhibited CD8 + cytotoxic phenotype and a JAK3 variant, while the CAR transgene was very low. The T cell clone was identified at low levels in the blood before CAR T infusion and in lung cancer. To assess the overall risk of secondary primary malignancy after commercial CAR T (CD19, BCMA), we analyzed 449 patients treated at the University of Pennsylvania. At a median follow-up of 10.3 months, 16 patients (3.6%) had a secondary primary malignancy. The median onset time was 26.4 and 9.7 months for solid and hematological malignancies, respectively. The projected 5-year cumulative incidence is 15.2% for solid and 2.3% for hematological malignancies. Overall, one case of TCL was observed, suggesting a low risk of TCL after CAR T. Profiling of a case of secondary T cell lymphoma following anti-CD19 CAR T cell therapy suggests that it was not caused by CAR insertional mutagenesis, with single-center analysis indicating that secondary T cell lymphoma risk after commercial CAR T cell treatment is low.